SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Elvira Elvira; Mohammad Badrul (JURNAL ILMIAH INFORMATIKA, 2022)
The existence of suppliers or suppliers plays an important role in the availability of raw materials for the ongoing production activities of a company. The role of suppliers is very vital in a company, so suppliers must maintain the availability of goods so that company activities can run smoothly. PT. Dutamasindo Labora Jaya is a company engaged in logistics and distribution. Companies are required to provide the best service to customers so that the company's performance remains stable and of course it is expected to increase as announced by the management. PT. Dutamasindo Labora Jaya is required to cooperate with many supplier companies to meet the company's operational needs. The problem faced by the company is the difficulty of determining which supplier has good performance in terms of delivery time, quality and quantity so that the company can prioritize these suppliers in meeting the raw materials needed. In this study, the author will implement a decision support system for selecting the best supplier using the simple additive weighting method.